Analisis Kebijakan Pembelajaran Jarak Jauh pada Pelajaran Bahasa Indonesia di Masa Wabah Virus Corona - Triyanto (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
This research aims to explore and describe a policy made by the government, specifically the policy related to distance learning during the Corona virus epidemic. The research method used is qualitative with a case study approach. Data collected were interviews with school principals, Indonesian language teachers, and observations in five classes, as well as distributing questionnaires with school principals, homeroom teachers, Indonesian language teachers, student guardians, and the students. Interview data were analyzed using